VARIATIONS IN THE LANGUAGE OF TRADERS AND BUYERS IN TRADITIONAL MARKETS IN THE PENINSULAR AREA IN DISCOURSE ANALYSIS APPROACH - Tiawati, Refa Lina; Maneechukate, Siriporn (ppjbsip, 2021)
The use of different vocabulary spoken by traders and buyers that cause language variations during buying and selling transactions in traditional markets on the coast with discourse analysis. This research aims to analyze language variations in terms of usage by traders and buyers in the wholesale market. This type of research is qualitative research using descriptive methods. The data source of this research is conversations conducted by merchants and buyers. The data in this study is a varied vocabulary. Data is analyzed using interactive models such as data reduction, presentation, and conclusion withdrawal. Based on the study results, it can be concluded that the variation in the spoken language of traders in the traditional market is as follows, language variations found as many as 7 language variations from 50 data. Variations of the language used are Indonesian as many as 9 conversations, Javanese, Minangkabau kumbung, Minangkabau language Talang Mandiangin, Minangkabau language dusun, Minangkabau language sirah river area, and Minangkabau language limpaso area.